UNDERWATER WARP TENSION METER - SIVA DAS, T K (Fishery Technology, 2025)
A self contained electronic solid-state instrument capable of measuring the tension between the different parts of a trawl net in operation, has been designed and developed for the measurement in the range 0 to 300 kg with an accuracy of Â± 2 kg. The instrument is useful for measuring the resistance to motion of various accessories of a trawl net. It consists of an inductive type underwater tension transducer and an electronic indicating meter kept on. board the vessel, both the units being connected by electric cable.